THE IMPACT OF NUTRICIONAL DEFICIENCIES ON THE DEVELOPMENT AND PROGRESION OF ALZHEIMER'S DISEASE (REMUNOM, 2025)
Costa, P. K. A. A. Neto G. R. C. The Impact of Nutritional Deficiencies on the Development and Progression of Alzheimer's Disease. 2025. 50p. Undergraduate Thesis (Nutrition) – Mario Pontes Jucá University Center, Maceió, 2025. Alzheimer's Disease (AD) is a progressive neurodegenerative condition that impairs essential cognitive functions, such as memory and reasoning. Several studies suggest that nutritional factors may play a significant role in both the development and progression of the disease. This work aims to analyze, through a literature review, the relationship between nutritional deficiencies and Alzheimer's Disease, with emphasis on the main nutrients whose absence can negatively impact brain health. The findings reinforce that nutritional interventions not only complement the conventional treatment of Alzheimer's Disease, but also represent essential strategies in its prevention. The adoption of adequate and individualized dietary practices can promote quality of life, delay disease progression, and offer metabolic and neuroprotective support to affected individuals.